The Promotion of Entrepreneurship as Catalyst for Inclusive Industrialization in South Africa - Matlala, Mpubane Emanuel; Ncube, Thandukwazi Richman (Economics and Entrepreneurship: The Proceedings of the 10\(^{th}\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
Entrepreneurship has long been recognized as a critical driver of economic growth, job creation, and innovation, particularly in the context of developing countries. In South Africa, entrepreneurship holds significant promise as a key component for fostering inclusive industrialization and advancing socio-economic development. The promotion of entrepreneurship within the industrialization agenda has the potential to empower marginalized communities, promote equitable access to economic opportunities, and drive sustainable economic growth. Despite the recognized importance of entrepreneurship in fostering inclusive industrialization, South Africa continues to face significant challenges in harnessing the full potential of entrepreneurship for economic development. Therefore, this study aims to assess the existing body of literature on the promotion of entrepreneurship as a catalyst for inclusive industrialization in South Africa. Specifically, seeking to identify key themes, challenges, and opportunities related to the integration of entrepreneurship into industrialization strategies in South Africa. The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure transparency, rigor, and reproducibility. A comprehensive search of multiple electronic databases, including Scopus (Elsevier), Web of Science, ScienceDirect, Sabinet, Education Resources Information Centre (ERIC), Journal Storage (JSTOR), and EBSCOhost, were conducted to identify relevant studies published between 2020-224. Key themes identified include the role of entrepreneurship in job creation, economic empowerment, and innovation within the industrialization context. The results highlighted the challenges such as access to finance, regulatory barriers, skills shortages, and market access constraints faced by entrepreneurs in South Africa. Additionally, the results identified opportunities for enhancing entrepreneurship through policy interventions, capacity-building initiatives, and stakeholder collaborations to foster inclusive industrial development. The study recommends the need for targeted policy interventions to address barriers to entrepreneurship, such as improving access to finance, streamlining regulatory processes, and enhancing skills development programs.